Variation in Adult and Juvenile Arrest Rates: The Influence of City Size and Metropolitan Environment - Lee, Chang-Bae (American journal of criminal justice, 2011)
Since the mid-1990s, the index crime rate has steadily decreased while the rate for Part II offenses has increased. The current study examines these differences from 1990 to 2004 using arrest rate data from the 35 largest cities in the state of Texas. Cluster regression analyses is employed to examine the effect of city size and city location, whether the city is part of a larger metropolitan area or “stand-alone,” to explain variation in juvenile and adult arrest rates by category of offense (violent, property, Part II) while controlling for the influence of social disorganization variables. Findings indicate that differences exist in the arrest rates for almost all types of offenses in mid-size versus very large cities. Contrasting adult versus juvenile arrest rates, city size and city location offer limited explanation for variation over time. Implications of these findings are discussed in the context of suggested policy and research directions.